A mathematical model for the design of distributed layout by considering production planning and system reconfiguration over multiple time periods - Farhad Shafigh; Fantahun M. Defersha; Soha Eid Moussa (Journal of Industrial Engineering International, 2015)
In this paper, we develop a new mathematical model that integrates layout configuration and production planning in the design of dynamic distributed layouts. The model incorporates a number of important manufacturing attributes such as demand fluctuation, system reconfiguration, lot splitting, work load balancing, alternative routings, machine capability and tooling requirements. In addition, the model allows several cost elements to be optimized in an integrated manner. These costs are associated with material handling, machine relocation, setup, inventory carrying, in-house production and subcontracting needs. Numerical examples of different sizes are presented to illustrate the nature of the developed model and shed light on several managerial insights.
Keywords: 650; Distributed layout; Dynamic reconfiguration; Production planning; Mixed integer linear programming